Lysosomal dysfunction in diabetic cardiomyopathy - Kobayashi, Satoru; Hahn, Younghee; Silverstein, Brett; Singh, Mandeep; Fleitz, Adeline; Van, Jennifer; Chen, Hongling; Liang, Qiangrong (Frontiers in Aging, 2023)
Diabetes is a major risk factor for a variety of cardiovascular complications, while diabetic cardiomyopathy, a disease specific to the myocardium independent of vascular lesions, is an important causative factor for increased risk of heart failure and mortality in diabetic populations. Lysosomes have been recognized as intracellular trash bags and recycling facilities. However, recent studies have revealed that lysosomes are a sophisticated signaling hub that regulates cell growth, division, differentiation, and even death, and play remarkably diverse roles in adapting cell metabolism to an ever-changing environment. Despite advances in our understanding of the physiological roles of lysosomes, the sequence in which these abnormalities occur and how they relate to the overall pathophysiology of the diabetic heart remain unclear and are under intense investigation. In this review, we summarize recent advances regarding the lysosomal injury and its consequences in diabetic cardiomyopathy.